Optimalisasi Manajemen Sistem Informasi melalui Big Data Analytics untuk Keberhasilan Transformasi Digital - Asri Agustin, Iska (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of Big Data Analytics (BDA) and Management Information Systems (MIS) on Digital Transformation (DT) and Organizational Readiness (OR) in facing the digital era. Employing a quantitative approach using Partial Least Squares - Structural Equation Modeling (PLS-SEM), data were collected from 30 organizations in Sukabumi City and Regency that have implemented or are in the process of implementing digital transformation. The results show that MIS has a significant and positive effect on both DT and OR, directly and indirectly through the mediation of digital transformation. In contrast, BDA does not exhibit a significant impact on either DT or OR, indicating that BDA implementation has yet to be strategically integrated within the organizations. Digital transformation is proven to be a significant mediator between MIS and OR but not between BDA and OR. The managerial implications highlight the importance of strengthening information systems, digital culture, and human resource capabilities in preparing organizations to face technological disruption. Theoretically, this study contributes to the development of a technology-based organizational readiness model and provides a foundation for more effective digital transformation strategies. Future research is recommended to expand the sectoral scope and include additional mediating or moderating variables for a more comprehensive understanding.